COMPARATIVE ANALYSIS OF TEACHING AND AESTHETIC PRINCIPLES IN CHINESE CLASSICAL DANCE AND CLASSICAL BALLET - Meng, Yuan; Vadhanasiriphongs, Bhannavichaya (Asia Pacific Journal of Religions and Cultures, 2025)
This article explores the distinct teaching systems and aesthetic principles of Chinese classical dance and classical ballet, focusing on their cultural, religious, and philosophical underpinnings. While both forms represent refined, long-established art traditions, they emerge from different cultural contexts that shape their respective techniques and expressive qualities. Chinese classical dance is deeply intertwined with traditional Chinese beliefs, including the principles of martial arts, Tai Chi, and opera, emphasizing fluidity, inner strength, and the harmonious balance of body and spirit. Its teaching system reflects the philosophical concepts of balance, breath control, and the spiritual connection between movement and the universe. In contrast, classical ballet, rooted in European history, particularly in Russian and French traditions, reflects ideals of elegance, discipline, and the pursuit of perfection, with an emphasis on symmetry and anatomical precision. Both forms are influenced by cultural values and, in some cases, religious beliefs. Chinese classical dance being linked to Confucian, Taoist, and Buddhist concepts, and ballet drawing on European ideals of grace, beauty, and transcendence. This comparative analysis examines how these beliefs and cultural frameworks shape the development of dance techniques, the teaching process, and the stylistic expression of both art forms. Ultimately, the article highlights the unique ways in which cultural and religious ideologies shape the teaching, performance, and perception of Chinese classical dance and classical ballet. This article presented (1) teaching methods of dance class in Chinese university, and (2) differences and characteristics between Chinese classical dance and classical ballet.